The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1182/blood.v83.9.2678.2678
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 inhibits interleukin-8 production in human neutrophils

Abstract: In highly purified human polymorphonuclear leukocyte (PMN) preparations containing less than 0.1% contaminating monocytes, significant amounts of interleukin-8 (IL-8) and small amounts of IL-1 alpha, IL-1 beta, and tumor necrosis factor-alpha (TNF-alpha) were produced by lipopolysaccharide (LPS) stimulation. Contrary to published reports, IL- 6 production could not be detected. IL-10 inhibited the production of IL-1 alpha, IL-1 beta, IL-8, and TNF-alpha in LPS-stimulated PMNs, as it did in human blood mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(64 citation statements)
references
References 24 publications
4
59
0
1
Order By: Relevance
“…Oligonucleotide primers were as follows: IL-8 (forward: AG-GAAGCTCACTGGTGGCTG and reverse: TAGGCACAATC-CAGGTGGC); IL-18 (forward: CAAGGAATTGTCTCCCAG-TGC and reverse: CAGCCGCTTTAGCAGCCA); Mip-1␣ (forward: AGCTGACTACTTTGAGACGAGCA and reverse: CG-GCTTCGCTTGGTTAGGA); Mip-1␤ (forward: CTGCTCTC-CAGCGCTCTCA and reverse: GTAAGAAAAGCAGCAGGC-GG); Mip-3␣ (forward: TCCTGGCTGCTTTGATGTCA and reverse: TCAAAGTTGCTTGCTGCTTCTG); Mip-3␤ (forward: GGCACCAATGATGCTGAAGA and reverse: GAAGTTCCT-CACGATGTACCCAG); TNF-␣ (forward: TCTTCTCGAAC-CCCGAGTGA and reverse: CCTCTGATGGCACCACCAG); 18S (forward: AGGAATTGACGGAAGGGCAC and reverse: GGACATCTAAGGGCATCACA). Contaminating PBMC mRNA was undetectable in our neutrophil preparations, as no cDNA could be amplified in RT-PCR using IL-6 primers in samples from LPS-stimulated cells, in agreement with previous studies (10,34).…”
Section: Isolation Of Rna and Real-time Pcr Analysessupporting
confidence: 92%
“…Oligonucleotide primers were as follows: IL-8 (forward: AG-GAAGCTCACTGGTGGCTG and reverse: TAGGCACAATC-CAGGTGGC); IL-18 (forward: CAAGGAATTGTCTCCCAG-TGC and reverse: CAGCCGCTTTAGCAGCCA); Mip-1␣ (forward: AGCTGACTACTTTGAGACGAGCA and reverse: CG-GCTTCGCTTGGTTAGGA); Mip-1␤ (forward: CTGCTCTC-CAGCGCTCTCA and reverse: GTAAGAAAAGCAGCAGGC-GG); Mip-3␣ (forward: TCCTGGCTGCTTTGATGTCA and reverse: TCAAAGTTGCTTGCTGCTTCTG); Mip-3␤ (forward: GGCACCAATGATGCTGAAGA and reverse: GAAGTTCCT-CACGATGTACCCAG); TNF-␣ (forward: TCTTCTCGAAC-CCCGAGTGA and reverse: CCTCTGATGGCACCACCAG); 18S (forward: AGGAATTGACGGAAGGGCAC and reverse: GGACATCTAAGGGCATCACA). Contaminating PBMC mRNA was undetectable in our neutrophil preparations, as no cDNA could be amplified in RT-PCR using IL-6 primers in samples from LPS-stimulated cells, in agreement with previous studies (10,34).…”
Section: Isolation Of Rna and Real-time Pcr Analysessupporting
confidence: 92%
“…IL-10. IL-10 appears in plasma by 1 h after endotoxemia and peaks by 3 h. Both IL-10 and PGE 2 work in part through cAMP pathways to turn off the production of inflammatory mediators in macrophages and PMNs [200][201]. Increases in intracellular cAMP in PMNs is associated with decreased adhesion to epithelial cells [202].…”
Section: Colony-stimulating Factorsmentioning
confidence: 99%
“…Since the protein synthesis inhibitor cycloheximide antagonizes the protective effects of IL-10, it was suggested that IL-10 may be responsible for the new synthesis of a ribonuclease acting on cytokine transcripts [16]. The ability of IL-10 to decrease mRNA stability has also been shown for a number of cytokines, including IL-6, IL-8, G-CSF, GM-CSF and IL-10 itself [14,15,17,18].…”
Section: Effect On In¯ammatory Cellsmentioning
confidence: 99%